Flexural Study of Reinforced Foamed Concrete Beam Containing Palm Oil Fuel Ash (POFA) and Eggshell Powder (ESP) as Partial Cement Replacement - Rahman, Amirul Faiz; Goh, W. I.; Jhatial, A. A. (International Journal of Sustainable Construction Engineering and Technology, 2019)
The fabrication process of concrete in the construction has caused carbon dioxide released into the atmosphere subsequently increases carbon footprint. Meanwhile, large sum of agricultural waste are generated such as palm oil fuel ash (POFA) and eggshell powder (ESP).  Incorporation of supplementary cementitious materials by capitalizing agricultural waste into concrete regarded as sustainable effort to reduce environmental impact. In this study, foamed concrete (FC-POFA-ES) was incorporated with 20% of POFA, 5% and 10% of ESP. Beam specimens 20 POFA 10 ESP has +14% and 20 POFA 05 ESP +13% higher ultimate load capacity but more severe cracking compared to control mix. The mix proportion of 20 POFA 10 ESP has better overall strength compared with control beam from experimental works. Therefore, it can be concluded the addition of POFA and ES powder has potential to be explored as cement replacement in foamed concrete structure